(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Throughout this article, our aim is to provide enough information on the methods of teaching foreign languages to preschoolers, as well as to research new innovative and interactive methods. Because nowadays foreign languages are being taught to children through elementary school, learning these languages is becoming increasingly popular.